2018
DOI: 10.1038/s41593-018-0164-7
|View full text |Cite
|
Sign up to set email alerts
|

Thalamic dual control of sleep and wakefulness

Abstract: Slow waves (0.5-4 Hz) predominate in the cortical electroencephalogram during non-rapid eye movement (NREM) sleep in mammals. They reflect the synchronization of large neuronal ensembles alternating between active (UP) and quiescent (Down) states and propagating along the neocortex. The thalamic contribution to cortical UP states and sleep modulation remains unclear. Here we show that spontaneous firing of centromedial thalamus (CMT) neurons in mice is phase-advanced to global cortical UP states and NREM-wake … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
192
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 195 publications
(214 citation statements)
references
References 60 publications
(112 reference statements)
20
192
1
1
Order By: Relevance
“…Optogenetic silencing of CMT neurons ( Fig. 4E) was previously shown to increase NREMS δ power during SD recovery sleep in the cingulate cortex, which receives direct input from the CMT (Gent et al, 2018a). We found that during CMT inhibition this increase was specific to the δ2 band, leaving δ1 activity unaffected ( Fig.…”
Section: Down-states (13 ± 3 and 4 ± 1 Hz Respectively)supporting
confidence: 51%
See 4 more Smart Citations
“…Optogenetic silencing of CMT neurons ( Fig. 4E) was previously shown to increase NREMS δ power during SD recovery sleep in the cingulate cortex, which receives direct input from the CMT (Gent et al, 2018a). We found that during CMT inhibition this increase was specific to the δ2 band, leaving δ1 activity unaffected ( Fig.…”
Section: Down-states (13 ± 3 and 4 ± 1 Hz Respectively)supporting
confidence: 51%
“…It has become increasingly clear that thalamocortical crosstalk is an important contributor to the generation of both the SO and δ-waves (Crunelli et al, 2015, Neske, 2015. For instance, cortical UP-states synchronize thalamic δoscillations (Steriade et al, 1991), which might contribute to the prominent nesting we observed of δ2-waves at δ1 onset, while excitatory thalamocortical input to the cortex can trigger cortical UP-state initiation and removing thalamic input reduces cortical SO period and synchrony (David et al, 2013, Lemieux et al, 2014, Gent et al, 2018a. Moreover, thalamic neurons are intrinsically capable of generating rhythmic oscillations at <1Hz frequencies (Blethyn et al, 2006, Crunelli et al, 2018, Fernandez et al, 2018, Halasz et al, 2014, Herrera et al, 2016 that could aid the strengthening of the cortical SO.…”
Section: Neuronal Substrates Of δ1 and δ2mentioning
confidence: 92%
See 3 more Smart Citations